ACTIVITY OF THE TEACHER OF HIGHER EDUCATION INSTITUTION IN THE CONDITIONS OF MODERNIZATION OF EDUCATION - M. Koldina (Вестник Мининского университета, 2017)
In article the purposes, components of professional and pedagogical activity, theoretical approaches to creation of models of professional and pedagogical activity of the teacher of the higher school in the conditions of modernization of education are considered.